Implications of Unclear Authority in Corporate Assets Forfeiture on the Effectiveness of Eradicating Money Laundering Crimes in Indonesia (International Forum of Researchers and Lecturers, 2025)
In order to determine who has the right to take business assets implicated in money laundering offenses, this paper examines the legal loophole in Law Number 8 of 2010 about the Prevention and Eradication of Money Laundering offenses (UU TPPU). The efficacy of law enforcement may be weakened and the process of recovering assets from crimes may be hampered by the ambiguous authority and lack of regulatory synchronization. Combining a statutory and conceptual approach with a normative legal technique, this study examines the implications of legal uncertainty on the mechanism of asset confiscation in eradicating TPPU. This research result indicates that the lack of authority in implementing asset forfeiture consequences results in inconsistent legal procedures, overlapping institutional roles, and slows down the recovery of state assets. Therefore, legal reform is needed through amendments to Article 9 of the TPPU Law and alignment with the Criminal Code (KUHP) and other related regulations so that the mechanism of asset confiscation is more precise, more effective, and coordinated. In addition, synergy between investigators, prosecutors, The Corruption Eradication Commission (KPK), and the Financial Transaction Reports and Analysis Center (PPATK) are essential for improving the efficiency of state asset recovery. Regulations and an integrated system make it possible to swiftly and publicly seize assets resulting from criminal activity, which deters criminals, enhances public trust in law enforcement, and ensures that assets obtained illegally can be returned for the benefit of the state and society, while reinforcing the integrity of the justice system.